The Influence of Above -the -Line and Below-the-Line Marketing Activities on Purchase Decisions of Hilo Sachet Products in Greater Malang, Indonesia - Made Budi Ramdani Kusuma; Windra Sigit Sinulingga; Helga Trinawati; Sri Astuti Pratminingsih; Alia Tri Utami (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the influence of Above-the-Line (ATL) and Below-the-Line (BTL) marketing activities on consumer purchase decisions regarding Hilo sachet products in the Greater Malang area of Indonesia. As marketing communication evolves with changing consumer behavior, the need for more targeted and impactful promotional strategies becomes essential, especially in the context of fast-moving consumer goods (FMCGs). A quantitative method was employed using survey data from 397 respondents who had recent purchase experience with Hilo sachets in Malang City, Batu City, and Malang Regency. The data were analyzed using multiple linear regression to determine the extent to which ATL and BTL activities affect consumer decision-making. Results show that both ATL and BTL activities significantly influence purchase decisions, with BTL exerting a slightly higher impact. This finding emphasizes the growing importance of personalized and direct marketing in regional consumer markets. This study contributes to the literature on integrated marketing communications by highlighting the comparative effectiveness of ATL and BTL strategies in influencing FMCG purchases in emerging market regions. The implications of this study provide guidance for marketers in allocating resources effectively between mass media and direct marketing efforts to enhance consumer engagement and conversion rates.